Monitoring and analyzing data from weather station in Universiti Malaysia Pahang - Nadiah, Haron (2018)
Weather data are important in our daily life as climate change leads to changes in precipitation. Weather station is one of the devices to collect the weather data. The weather data such as precipitation, humidity, temperature, and wind speed are collected by using this device. The data such as rainfall and temperature are used to serve as a precautionary measure to against natural calamity or disaster such as flood and drought. The weather data collected for a long period are used to predict the climate change in future trends. Besides, the rainfall pattern in University Malaysia Pahang (UMP) is determined by analyzing the data of rainfall and temperature in UMP Pekan and Gambang station. All the data are analyzed to check the minimum monthly data for every year starting from 2015 until 2017. In order to check the trend of rainfall data at UMP (Gambang and Pekan), maximum data of rainfall received for that month also are analyzed. The analysis also start from year 2015 until 2017. The rainfall pattern in UMP area are determined from the data analysis.